Severe respiratory viral infection induces procalcitonin in the absence of bacterial pneumonia. Issue 11 (21st August 2020) - Gautam, Samir; Cohen, Avi J; Stahl, Yannick; Valda Toro, Patricia; Young, Grant M; Datta, Rupak; Yan, Xiting; Ristic, Nicholas T; Bermejo, Santos D; Sharma, Lokesh; Restrepo, Marcos I; Dela Cruz, Charles S
Abstract : Introduction: Procalcitonin expression is thought to be stimulated by bacteria and suppressed by viruses via interferon signalling. Consequently, during respiratory viral illness, clinicians often interpret elevated procalcitonin as evidence of bacterial coinfection, prompting antibiotic administration. We sought to evaluate the validity of this practice and the underlying assumption that viral infection inhibits procalcitonin synthesis. Methods: We conducted a retrospective cohort study of patients hospitalised with pure viral infection (n=2075) versus bacterial coinfection (n=179). The ability of procalcitonin to distinguish these groups was assessed. In addition, procalcitonin and interferon gene expression were evaluated in murine and cellular models of influenza infection. Results: Patients with bacterial coinfection had higher procalcitonin than those with pure viral infection, but also more severe disease and higher mortality (p<0.001). After matching for severity, the specificity of procalcitonin for bacterial coinfection dropped substantially, from 72% to 61%. In fact, receiver operating characteristic curve analysis showed that procalcitonin was a better indicator of multiple indices of severity (eg, organ failures and mortality) than of coinfection. Accordingly, patients with severe viral infection had elevated procalcitonin. In murine and cellular models of influenza infection, procalcitonin was also elevated despite bacteriologic sterility and correlated with markers of severity. Interferon signalling did not abrogate procalcitonin synthesis. Discussion: These studies reveal that procalcitonin rises during pure viral infection in proportion to disease severity and is not suppressed by interferon signalling, in contrast to prior models of procalcitonin regulation. Applied clinically, our data suggest that procalcitonin represents a better indicator of disease severity than bacterial coinfection during viral respiratory infection.